TINJAUAN ATAS PENERAPAN AKUNTANSI ASET TETAP PADA PT BLUE BIRD TBK BERDASARKAN PSAK 16 - Nurma Gupita Ayuningtyas (Jurnal Acitya Ardana, 2022)
ABSTRACT The preparation and presentation of the company's financial statements in Indonesia based on the Financial Accounting Standards. PT Blue Bird Tbk is the pioneer of taxi industry in Indonesia which officially go public at Indonesia Stock Exchange on November 14, 2014. Therefore, the financial statements of PT Blue Bird Tbk should be prepared based on the applicable Financial Accounting Standards in Indonesia. A fixed asset is one of several components contained in the financial statements, notably in the statement of financial position. The entity must determine the appropriate and adequate fixed asset management policy because it has an important role. This research aims to review the application of the accounting fixed asset at PT Blue Bird Tbk based on the Statement of Financial Accounting Standards (PSAK) 16 about the acquisition up to presentation and disclosure of financial statements for PT Blue Bird Tbk's financial statements as of 2019 (audited). The method used in this research is quantitative in the form of a library method. Based on the research results, PT Blue Bird Tbk passably and adequately implemented the PSAK 16, ‘Property, plant, and equipment’.